Pengaruh Konflik Terhadap Pembangunan Pendidikan Di Aceh - Amin, Khairul (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2018)
This paper aims to discuss how the impact of conflict on the development of education in Aceh today, because Aceh as a conflict area have different conditions with other areas in indonesia, especially in the development of education. This paper is prepared using a literature study approach, in which data are collected from secondary sources in the form of documents related to current educational development, as well as the results of research related to conflict and educational development. Current conditions indicate that Aceh's educational participation is growing rapidly and exceeding than other areas not affected by the conflict. Conflict has contributed to the acceleration of educational development for the people of Aceh today. The success of educational development is indicated by the increasing number of educational development indicators (APS, APM, HLS, ARLS etc) that surpass the national average. When compared to other areas not exposed to conflict, the development of education in Aceh is quite successful.